Prodstar - an application of MRP II software to production planning and control / Muzafar Ahamad,Mamat Tarmizi Abdul Ghani and Musa Mohd Ehsan - Ahamad, Muzafar; Abdul Ghani, Mamat Tarmizi; Mohd Ehsan, Musa (Faculty of Mechanical Engineering, 1996)
Every day managers make decisions without knowing what will happen in the future . Inventory is ordered without certainly as to what sales will be ; new equipment is purchased despite uncertainty about demand for products ; and investments are made without knowing what profits will be . Managers are always trying to make batter estimates of what will happen in the future in the face of uncertainty . Making good estimates is the main purpose of forecasting . In this chapter we examine different types of forecasts , and we present a variety of forecasting models with such names as moving averages , exponential smoothing , and linear regression . The purpose is to show that there are many ways for managers to forecast the future . We also provide an overview of the subject of business sales forecasting and describe how to prepare , monitor , and judge the accuracy of a forecast . Good forecasts are an essential part of efficient service and manufacturing operations ; they are also an important modeling tool in both strategic and tactical decision making.